The calculated values of wind load with a given probability - Y. V. Krasnoschekov; M. Y. Zapoleva (Вестник СибАДИ, 2017)
The authors analyze probabilistic models of a static component of wind load and compare the calculated values obtained for each of the models with different "urgent" probability. The authors conclude that the probability of wind load’s normative values of the limiting state’s method corresponds to 5 - year period, and the calculated values - to 50 - year old. There are presented tables with the calculated values of wind load for all wind areas that are handy in designing high buildings.